Pengaruh Lingkungan Keluarga Terhadap Minat Baca pada Siswa Kelas VIII di SMP Negeri 2 Kubung (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the influence of the family environment on the reading interest of eighth-grade students at SMP Negeri 2 Kubung. The study used a quantitative approach with an associative research type. The study population was all 88 eighth-grade students of SMP Negeri 2 Kubung, with a sampling technique using total sampling. Data were collected through questionnaires and analyzed using simple regression analysis. The results showed that the family environment had a positive and significant effect on students' reading interest, indicated by a significance value of 0.000 (